2020
DOI: 10.1177/0145721720906082
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Influences on Physical Activity Among Low-Income African American Adults With Type 2 Diabetes Mellitus

Abstract: Purpose The purpose of the study was to explore the influences of the neighborhood environment on physical activity (PA) among people living with type 2 diabetes mellitus (T2DM) in a community with limited resources. Methods Participants were adults with T2DM and their family members or friends who help in the management of T2DM and who were living in a low-income African American (AA) community. Health care providers working in the neighborhood were also included. Using an emergent design, qualitative data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 36 publications
(47 reference statements)
2
10
0
Order By: Relevance
“…Many structural aspects in the neighbourhoods, such as lack of proper lighting, crowded sidewalks, lack of green spaces, and dense traffic were mentioned by the study participants. This is in line with previous research, which equally highlighted the negative effect of poor infrastructure, such as irregular roads and pavements [30], neighbourhood insecurity [31], or the lack of recreational facilities on physical activity of patients with type 2 diabetes [32]. A higher neighbourhood walkability supports physical activity also in overweight and obese adults with metabolic syndrome [33].…”
Section: Discussionsupporting
confidence: 90%
“…Many structural aspects in the neighbourhoods, such as lack of proper lighting, crowded sidewalks, lack of green spaces, and dense traffic were mentioned by the study participants. This is in line with previous research, which equally highlighted the negative effect of poor infrastructure, such as irregular roads and pavements [30], neighbourhood insecurity [31], or the lack of recreational facilities on physical activity of patients with type 2 diabetes [32]. A higher neighbourhood walkability supports physical activity also in overweight and obese adults with metabolic syndrome [33].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, and consistent with previous reports in oncology patients (Courneya et al, 2014; van Waart et al, 2015; Wilcoxon et al, 2020; Witlox et al, 2019) and the general population (Puciato et al, 2018; Schmidt et al, 2017; Scholes & Bann, 2018), patients in our NoEx group reported fewer years of education and had a lower annual household income. Barriers to regular exercise in individuals who are socioeconomically disadvantaged may include: neighborhood safety concerns; lack of recreation centers, parks, and gyms (Park et al, 2020); as well as lack of social support and time for exercise (Clifford et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…8 Physical activity (PA) is a key behavior for the prevention of obesity and other NCDs; 9 yet, numerous barriers for PA have been found for populations experiencing economic disadvantage in the United States, including distance and lack of access to PA facilities, perceived neighborhood safety, and lack of social and community supports. [10][11][12][13] In Austin, Texas, more than one-quarter of adults are obese (29%), with low-income residents experiencing a disproportionate burden. 14,15 Based on recent estimates, half of Austin and Travis County adults (50.3%) do not meet PA recommendations.…”
Section: Family and Community Healthmentioning
confidence: 99%